(10x+9)=(4x+1)

Simple and best practice solution for (10x+9)=(4x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (10x+9)=(4x+1) equation:



(10x+9)=(4x+1)
We move all terms to the left:
(10x+9)-((4x+1))=0
We get rid of parentheses
10x-((4x+1))+9=0
We calculate terms in parentheses: -((4x+1)), so:
(4x+1)
We get rid of parentheses
4x+1
Back to the equation:
-(4x+1)
We get rid of parentheses
10x-4x-1+9=0
We add all the numbers together, and all the variables
6x+8=0
We move all terms containing x to the left, all other terms to the right
6x=-8
x=-8/6
x=-1+1/3

You can always share this solution

See similar equations:

| x^2?7x+2=0 | | 11x5=8x-6 | | 5(3m-2)-9(5-2m)=4m+2(5m+1) | | 2x2=300 | | 5(3m-2)-9(5-2m)=4m+2(5m+1 | | 3x+4=5-9 | | 9/x=98/7 | | 3x+17=32;3 | | 5x+3=15x+7 | | 261=152-v | | 5x+3+15x+7=180 | | 4x+5=17;3 | | 8/x^2-1-4/x-1=2/x+1 | | 23=3/1b–2+3/4b | | (4x-25)(2x-1)=180 | | 8y+–11y+8=17 | | -13+p=-10 | | 1.5x-(6)=7.5 | | 7x+4-2x=10x+16 | | 2x?3+4x=29 | | -x-20=6x+1 | | -4x-(18)=22 | | a+7-3(2a+5)=-2(a-15)-5 | | X+19=2x-20;-1 | | x/5-3x+7/10=1 | | 3u+64=11u | | f(2)=1.5(2)+1 | | 8(x-3)=8x+40 | | 2x-14+2x=4(4x-5)+2 | | 3=1,5b | | | | | | 64=48/x |

Equations solver categories